Dinucleoside polyphosphates act as 5'-RNA caps in bacteria - Hudeček, Oldřich; Benoni, Roberto; Reyes-Gutierrez, Paul E; Culka, Martin; Šanderová, Hana; Hubálek, Martin; Rulíšek, Lubomír; Cvačka, Josef; Krásný, Libor; Cahová, Hana (Nature communications, 2020)
It has been more than 50 years since the discovery of dinucleoside polyphosphates (NpnNs) and yet their roles and mechanisms of action remain unclear. Here, we show that both methylated and non-methylated NpnNs serve as RNA caps in Escherichia coli. NpnNs are excellent substrates for T7 and E. coli RNA polymerases (RNAPs) and efficiently initiate transcription. We demonstrate, that the E. coli enzymes RNA 5'-pyrophosphohydrolase (RppH) and bis(5'-nucleosyl)-tetraphosphatase (ApaH) are able to remove the NpnN-caps from RNA. ApaH is able to cleave all NpnN-caps, while RppH is unable to cleave the methylated forms suggesting that the methylation adds an additional layer to RNA stability regulation. Our work introduces a different perspective on the chemical structure of RNA in prokaryotes and on the role of RNA caps. We bring evidence that small molecules, such as NpnNs are incorporated into RNA and may thus influence the cellular metabolism and RNA turnover.
Keywords: RNA Stability; konformace nukleové kyseliny; dinukleosidfosfáty; Nucleic Acid Conformation; proteiny z Escherichia coli; DNA řízené RNA-polymerasy; metylace; RNA, Bacterial; Acid Anhydride Hydrolases; DNA-Directed RNA Polymerases; hydrolasy působící na anhydridy kyselin; Escherichia coli; RNA čepičky; bakteriální RNA; RNA Caps; Escherichia coli Proteins; Dinucleoside Phosphates; Methylation; stabilita RNA